Structure and microbial synthesis of sub-10 nm Bi2O3 nanocrystals - Uddin, Imran; Adyanthaya, Suguna D.; Syed, Asad; Selvaraj, K.; Ahmad, Absar; Poddar, Pankaj (Journal of Nanoscience and Nanotechnology, 2008)
After the advent of novel chemical and microbial techniques, providing control over grain size and shape of the nanomaterials, several binary-oxide materials have been explored in size less than 10 nm for their tunable physical properties. Bi2O3 nanoparticles have also redrawn attention due to their excellent properties, mostly as optoelectronic material. Here, we report the room-temperature biosynthesis of Bi2O3 nanoparticles in a size range of 5-8 nm by extra-cellularly challenging the plant pathogenic fungus-Fusarium oxysporum with the bismuth nitrate as precursor. The as-synthesized particle-surfaces are inherently functionalized by a robust layer of proteins which provides them very good stability in the aqueous medium. Structural investigation using selected area electron diffraction, high resolution transmission electron microscopy and powder XRD shows that particles are almost perfectly single crystalline and primarily crystallize in alpha-phase with monoclinic structure.
Keywords: Biosynthesis; fungi; High Refractive Index; High Resolution TEM; Nanoparticles